First-time seizure revealing late-onset Fahr’s disease: a case report and brief literature review - Lamessa, Adugna; Tesfaye, Kenna; Woyimo, Tamirat Godebo; Gebremichael, Ermias Habte (Frontiers in Human Neuroscience, 2024)
Fahr’s disease (FD), otherwise known as primary familial brain calcification, is a rare neurodegenerative condition that involves intracerebral calcification at the level of the basal ganglia and other brain regions. It is an inherited neurologic disorder, although its molecular genetics have not been thoroughly defined. Patients usually present with a wide range of symptoms, predominantly movement disorders and cognitive changes. However, seizures are a rare initial presenting features of late-onset FD in adults. Herein, we present the case of a 60-year-old man with no known chronic illnesses who was admitted to a tertiary hospital after experiencing first-time generalized tonic-clonic seizures and loss of consciousness for two days. Basic laboratory results were within normal limits, and a non-contrast brain computed tomography (CT) scan showed intracerebral calcification. The patient was diagnosed with epilepsy secondary to FD based on its modified diagnostic criteria and responded well to antiepileptic treatment. The case highlights a rare association and emphasizes the importance of considering this diagnosis in patients experiencing an inaugural seizure; appropriate tests should be performed to confirm or rule out other relevant and secondary causes, and the treatment should be modified accordingly.